Communicative Language Teaching with Realia to Enhance Students’ English Vocabulary - Patmi, Resky Indrayana Uda; Sabaruddin, Sabaruddin (JLE: Journal of Literate of English Education Study Program, 2021)
This research discusses vocabulary improvement of second year student at Madrasah Tsanawiyah Madani Pao-pao, South Sulawesi, Indonesia using Communicative Language Teaching with Realia. Researchers intend to answer the question "Is the use of Realia in Madrasah Tsanawiyah Madani Pao-pao effective in improving the vocabulary of second-grade students in communicative language teaching (CLT)?" This study aims to understand how CLT and Realia improve the vocabulary of Islamic school students. This study applied a real experimental method of two variables: the independent variable (CLT with Realia) and the dependent variable (vocabulary mastery). In this study, 60 students were randomly selected to participate, 30 in the experimental class and 30 in the control class. This study uses a written vocabulary test as a tool. From the data analysis point of view, the students' vocabulary has improved significantly. It can be seen from the results of the average score of the control category (71.8) and the average score of the control category (63.8). From the research findings and discussions, it can be concluded that the application of CLT and Realia can improve students’ vocabulary in Madrasah Tsanawiyah Madani Pao-pao.